The epidemiology and microbiological characteristics of infections caused by Gram-negative bacteria in Qatar: national surveillance from the Study for Monitoring of Antimicrobial Resistance Trends (SMART): 2017 to 2019 - Mazen A Sid Ahmed (17945099) (2023)
Background The global Study of Monitoring Antimicrobial Resistance Trends (SMART) is a surveillance program for evaluation of antimicrobial resistance (AMR) in Gram-negative bacteria (GNB) from different regions including Gulf countries. Objectives To evaluate AMR in GNB from various clinical specimens including microbiological and genetic characteristics for existing and novel antimicrobials. Methods A prospective study was conducted on clinical specimens from Hamad Medical Corporation, Qatar, between 2017 and 2019 according to the SMART protocol. Consecutive GNB from different sites were evaluated including lower respiratory, urinary tract, intrabdominal and bloodstream infections. Results Over the 3 years study period, 748 isolates were evaluated from the specified sites comprising 37 different GNB outlining four key pathogens: Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa and Stenotrophomonas maltophilia. For the two major pathogens E. coli and K. pneumoniae, phenotypic ESBL was identified in 55.77% (116/208) compared to 39% (73/187), while meropenem resistance was 3.8% compared to 12.8% and imipenem/relebactam resistance was 2.97% compared to 11.76%, respectively. The overall ceftolozane/tazobactam resistance for E. coli was 9.6% (20/208) compared to 14.97% (28/187) for K. pneumoniae while resistance for ceftazidime/avibactam was 3.65% (5/137) and 5.98% (10/117), respectively. Genomic characteristics of 70 Enterobacterales including 48 carbapenem-resistant, revealed prevalence of β-lactamases from all classes, predominated by blaCXM-15 while carbapenem resistance revealed paucity of blaKPC and dominance of blaOXA-48 and blaNDM resistance genes. Conclusions Surveillance of GNB from Qatar showed prevalence of key pathogens similar to other regions but demonstrated significant resistance patterns to existing and novel antimicrobials with different underlying resistance mechanisms. Other Information Published in: JAC-Antimicrobial Resistance License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jacamr/dlad086